Trade Unions on YouTube Online Revitalization in Sweden - Jansson, Jenny; Uba, Katrin (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"Trade Unions on YouTube provides a much-needed assessment of how old social movement actors employ new social media platforms to promote themselves and their activities today. A must-read for trade unions scholars and activists alike, this book illustrates how, in the age of digital media, there is more than one pattern towards trade union revitalization and each of them implies different communicative challenges."-Alice Mattoni, Associate Professor at the Department of Political and Social Sciences, University of Bologna, Italy This book investigates how trade unions representing different social classes use YouTube videos for renewal purposes. Information and communication technology has undoubtedly offered new opportunities for social movements, but while research suggests that these new means of communication can be used for trade union revitalization, few studies have examined what unions actually do on socialmedia. By analysing more than 4500 videos that have been uploaded by Swedish trade unions, Jansson and Uba explore how unions use YouTube to address issues such as recruiting new members, improving internal democracy, promoting political campaigns and constructing (new) self-images. The results demonstrate that trade unions representing a range of social classes use different revitalization strategies via YouTube. This research will be of use to students and scholars researching European politics and political participation, trade unionism and labour movements in the digital age. .